Use of multimedia and the world wide web in civil engineering learning - Golias, Mihalis; Angelides, Demos C.; Marnas, Stelios I.; Vrakas, Dimitris (My University, 2005)
The case study method, which has been proven to be a very useful learning tool, can be further enhanced with the use of multimedia and the World Wide Web. This paper demonstrates multimedia and Web-based enhancement with the design and construction of a port, a large-scale civil engineering project. The main purpose was to create an educational tool that brings into the classroom a "real-life" design and construction problem, including the construction field, operation of equipment, and details of construction methods. This enables civil engineering students to better understand the details of the planning, design, and construction of a complicated project. Furthermore, through the use of evaluation tests, feedback on the students' understanding of the case study can be provided to both the students and the educator. This application can be expanded beyond an academic environment for use as a learning tool in a business environment, which may be especially beneficial for new engineers. © ASCE.